2011 11th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing 2011
DOI: 10.1109/ccgrid.2011.50
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Performance of Parallel Applications on Multi-socket Virtual Machines

Abstract: Abstract-In this paper we characterize the behavior with respect to memory locality management of scientific computing applications running in virtualized environments. NUMA locality on current solutions (KVM and Xen) is enforced by pinning virtual machines to CPUs and providing NUMA aware allocation in hypervisors. Our analysis shows that due to two-level memory management and lack of integration with page reclamation mechanisms, applications running on warm VMs suffer from a "leakage" of page locality. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Further investigation of the impact of the memory cache was out of the scope of this project. Other studies have shown the effects of memory performance in VMs [43] …”
Section: Spec Cpumentioning
confidence: 99%
“…Further investigation of the impact of the memory cache was out of the scope of this project. Other studies have shown the effects of memory performance in VMs [43] …”
Section: Spec Cpumentioning
confidence: 99%
“…The listing is intended to identify vulnerabilities to indicate that although the technology may be relatively new to an enterprise environment, the amount of implications evident in the products is growing as use increases. To mitigate the risk associated with rogue or phantom virtualization architectures, as well as unpatched or improperly patched VMs, the following are several security recommendations aimed at securing these types of environments: [20]. Deny all write, copy, and execute access to this directory, except for an administrative role associated with virtualization management.…”
Section: Recommendationsmentioning
confidence: 99%
“…The key element becomes this decoupling of the logical resource from the physical resource where the current programs and data in use are held, which can affect performance. Virtualization technologies attempt to provide high virtualized system performance through open source solutions such as kernel-based VMs [20], Xen [2] and proprietary solutions such as Intel's VT-x and VT-I [54] and HyperDealer [19].…”
Section: Introductionmentioning
confidence: 99%
“…By deploying a secure multi-tenant virtual service provision mechanism, each business unit benefits from the transparency of the virtual environment [15]. Hence, a multi-tenancy architecture enables the provision of new services quickly and cost effectively by using Service Level Agreements (SLAs) [17], [14].…”
Section: Related Workmentioning
confidence: 99%